2010
DOI: 10.1016/j.scitotenv.2010.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the noncovalent binding interactions between polycyclic aromatic hydrocarbon metabolites and human p53 cDNA

Abstract: The binding of reactive polycyclic aromatic hydrocarbon (PAH) metabolites, formed enzymatically, to DNA is a crucial step in PAH carcinogenesis in vivo. We investigated the noncovalent binding interactions between 11 PAH metabolites and human p53 complementary DNA (p53 cDNA) using the fluorescence displacement method and molecular docking analysis. All of the examined metabolites predominantly interacted with p53 cDNA by intercalation instead of groove binding. The dissociation constants ranged from 0.02 to 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…A comparison of the perfluoroalkyl sulfonates and perfluorocarboxyl acids with the same number of carbons showed that PFOS and PFBS had stronger binding affinities than PFOA and PFBA, respectively. Hydrogen bonds have been proposed to form between the fluorine and oxygen atoms of the ligand and DNA upon interaction (Wei et al 2010). Consequently, as there are more donor fluorine and oxygen atoms on the perfluoroalkyl sulfonates than on the perfluorocarboxyl acids with same number of carbons, it is likely that more hydrogen bonds form, thereby accounting for the observed stronger affinity of PFOS and PFBS to DNA than PFOA and PFBA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A comparison of the perfluoroalkyl sulfonates and perfluorocarboxyl acids with the same number of carbons showed that PFOS and PFBS had stronger binding affinities than PFOA and PFBA, respectively. Hydrogen bonds have been proposed to form between the fluorine and oxygen atoms of the ligand and DNA upon interaction (Wei et al 2010). Consequently, as there are more donor fluorine and oxygen atoms on the perfluoroalkyl sulfonates than on the perfluorocarboxyl acids with same number of carbons, it is likely that more hydrogen bonds form, thereby accounting for the observed stronger affinity of PFOS and PFBS to DNA than PFOA and PFBA.…”
Section: Resultsmentioning
confidence: 99%
“…The PDB contains extensive information regarding the structures of ligand-DNA complexes, and three structures of these complexes were used to establish the PFAA-DNA intercalation or the minor groove binding model to explore the binding interactions. Ellipticine intercalated into the sequence d(CGATCG) 2 (1Z3F) was selected because this structure had been used to successfully explore the intercalation of pollutants with DNA (Wei et al 2010). The second intercalation model (108D), d(CGCTAGCG) 2 complexed with the bis-intercalator 1, 1′-(4,4,8,8-tetramethyl-4,8-diazaundecamethylene)bis[4-(3-methyl-2,3-dihydrobenzo-1,3-thiazolyl-2-methylidene)quinolinium] tetraiodide (TOTO), was selected because the binding mode of TOTO is similar to that of TO (Hansen et al 1996).…”
Section: Conformational Changes To Dna Upon Interaction With Pfaasmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a clear morphological change of calf thymus DNA (CT-DNA) from linear type to condensation form was observed after binding with 9-hydroxyfluorene in atomic force microscopy (Wang et al, 2009a). Recently, Wei et al (2010) also reported that 11 PAHs metabolites predominantly interacted with human p53 DNA by intercalation instead of groove binding. However, the detail mechanisms of DNA binding associated with HO-PAHs remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, hydroxylated PAHs (HO-PAHs) have emerged and are causing increasing concern due to their detection in human hair (Schummer et al, 2009), urine (Campo et al, 2010Li et al, 2010c), and expired air samples (Li et al, 2010c); these agents have even been found in the bile of deep-sea fish (Escartin and Porte, 1999). Previous studies have shown that certain HO-PAHs can affect hormone homeostasis, as they act as potent ligands for binding to the aryl hydrocarbon receptor (AhR) and even interact with DNA (Wang et al, 2009a;Wenger et al, 2009;Ohura et al, 2010;Wei et al, 2010). For instance, it was reported that 5 HO-PAHs (2-hydroxychrysene, 2-hydroxyphenanthrene, 1-hydroxypyrene, 2-hydroxynaphthalene and 1-hydroxynaphthalene), which showed structural similarities to 17␤-estrodiol, exhibit estrogenic activities (Wenger et al, 2009).…”
Section: Introductionmentioning
confidence: 99%